Investment competition among Swiss ski areas - Pascal Troxler; Monika Bandi Tanner; Marcus Roller (Annals of Tourism Research Empirical Insights, 2025)
In recent years, ski area operators in Switzerland have faced decreasing demand while ski lift and snowmaking capabilities have increased - partly using financial aid from public funds. It is therefore crucial to determine to what extent ski area investment supports demand and affects the competition for the remaining guests. Exploiting firm-level and natural snowpack data, we find that ski areas with above-median snowmaking capabilities decrease their natural snow dependency and that ski lift investments induce a positive, albeit small, effect on outcomes in the winter following their construction. Additionally, we document adverse effects on demand for nearby neighboring ski area expansions. The results imply that investments in high-capacity lifts are relatively ineffective at retaining demand and sustaining revenue.
Keywords: 330; Investment competition; Ski area expansion; Ski area operators; Ski lift replacement; Snowmaking; Spatial competition